Peran Komunikasi Orang Tua Dengan Pihak Sekolah Tadika Didik Bestari Gemilang Dalam Layanan Anak Autisme di Lembaga Pendidikan Anak Usia Dini - Deswita (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to analyze the role of inclusive education in optimizing the development of children with autism, with a focus on the Tadika Didik Bestari Gemilang School in Malaysia. The research method used is a case study with a qualitative approach. Data collection techniques used in this research include interviews, in-depth observations with parents and teachers and documentation studies at the research location. The data analysis technique used is qualitative data analysis technique, which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that BL, a child with autism, experienced significant positive changes in social interaction, language, behavior and fine motor skills after joining an inclusive school. Effective collaboration between parents, teachers, and special educators in schools plays a crucial role in supporting BL development. The conclusion of this research is that inclusive education not only facilitates the active participation of children with autism in the learning process, but also supports them in achieving their full potential in a supportive educational environment.